Multi-level governance tackling the COVID-19 pandemic in China - de Andrade e Silva Forte dos Santos, Niedja (2021)
This paper investigates China’s leadership over intergovernmental and private actions in tackling the COVID-19 pandemic and identifies sectors, levels, and roles played. The main argument is that successful control over the pandemic depends on effective and integrated leadership at different levels. The conceptual, theoretical, and analytical framework is given by the multi-level governance theory. Through a case study, the actions adopted in China (n = 374) were mapped from reports issued by the Chinese government, the World Health Organization, and media information. Content analysis was adopted to categorize data. Quantitative and qualitative findings show different roles of actors, as well as usefulness of the multi-level governance to provide fast and complex responses required during the pandemic. In the last section, the conclusion and recommendations for future research are addressed. The lack of studies on the application of multi-level governance in non-democratic regimes especially during a pandemic indicates the relevance and contribution of this study to the literature.